Cancer‐related help‐seeking in cancer survivors living in regional and remote Australia. Issue 7 (23rd February 2021) - Goodwin, Belinda C.; Chambers, Suzanne; Aitken, Joanne; Ralph, Nicholas; March, Sonja; Ireland, Michael; Rowe, Arlen; Crawford‐Williams, Fiona; Zajdlewicz, Leah; Dunn, Jeff
Abstract: Objectives: To measure rates of detection via screening, perceived self‐imposed delays in seeking medical attention, and support seeking in a sample of regional and remote people with a cancer diagnosis and to test whether an association exists between these behaviours and minimising problems and resignation, a need for self‐control and reliance and fatalism. Correlations and binary logistic regressions were conducted to test the associations between demographic characteristics, attitudes and behaviours. Results: Females were more likely to have had their cancer detected via screening (OR = 10.02, CI = 3.49–28.78). Younger participants ( r = −0.103, p = 0.009) were slightly more likely to seek at least one form of support and online support was sought more often by younger patients ( r = −0.269, p < 0.001), females ( r = 0.152, p < 0.001), those from higher socio‐economic (SES) areas ( r = 0.100, p = 0.012), and those with higher education levels ( r = 0.247, p < 0.001). Younger ( r = −0.161, p < 0.001), and female ( r = 0.82, p = 0.013), participants were also slightly more likely to seek support specifically through cancer support groups. No significant relationships between minimising problems and resignation, needs for control and self‐reliance or fatalism and detection via screening, support seeking, or perceived self‐imposed delays to seeking medical attention were apparent, with the exception that those with higher fatalism (predetermined health) were slightly less likely to report seeking support or information online (OR = 0.79, CI = 0.65–0.95) and slightly more likely to report using Cancer Council's support services (OR = 1.24, CI = 1.02–1.52). Conclusions: Strategies to improve the accessibility and appropriateness of support available for regional and remote cancer patients should consider interventions that remove barriers to access associated with age, gender, and education as opposed to those which address the attitudinal traits measured here.